Selected school-related correlates of the performance of Home Economics graduates in Region 8 in the licensure examination for teachers (LET) - Bustamente, Hilaria Lobo (2001)
This study examined the performance of home economics graduates in the Licensure Examination for Teachers (LET) in six state colleges in Region 8. The respondents of the study were 134 home economics graduate examinees and 60 home economics teachers/administrators. Data on the home economics graduate examinees were obtained from the Professional Regulation Commission's results of the LET, students' school records, and from the questionnaire developed by the researcher for teacher respondents. Descriptive statistics, Wilcoxon test and Spearman's Rank Order of Coefficient Correlation were the statistical tools used. The home economics graduate in Home Economics, Home Technology and Home Economics and Technology. Majority of the home economics teachers teaching home economics courses were home economics major, with units in Ph.D./Ed.D., committed to teaching, direction setters, goal oriented and used a variety of teaching strategies but have attended few training/seminars. The colleges' vision and or mission was in accordance to government's regional and national thrust, admission policies are similar, curricular offerings and institutional facilities are adequate, with favorable organizational climate and provides strong structure support to instruction. The home economics graduate examinees performed better in the Licensure Examinees for Teachers (LET). No significant difference was found in the performance of home economics graduates in the LET between 1997 and 1998, however, the performance of the elementary and secondary levels examinees manifested a significant difference. Age was significantly and negatively correlated with professional education test, the younger the graduate examinees, the better is their performance in the Professional Education portion of the LET. Food laboratory facilities were also significant and negatively correlated with the general education test. The better the facilities in food laboratory, the lower is the performance in the general education section of the LET.